2022
DOI: 10.1186/s12902-022-01143-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose spironolactone ameliorates adipose tissue inflammation and apoptosis in letrozole-induced PCOS rat model

Abstract: Background of study Globally, many reproductive aged women are affected by polycystic ovarian syndrome (PCOS), which is a common endocrine and metabolic disorder that is linked with adipose dysfunction and chronic low-grade inflammation. Spironolactone (SPL), a mineralocorticoid receptor blocker has been documented as a metabolic modulator. However, its immunomodulatory effect in PCOS is unknown. Therefore, the present study hypothesized that SPL would ameliorate adipose dysfunction and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Earlier studies suggested that chronic oxidative stress results in inflammatory process, tissue remodeling and apoptosis ( Ye et al, 2023 ). LET n the earlier studies have increased the markers of inflammation and apoptosis, suggesting its mechanism in PCOS ( Areloegbe et al, 2022 ). Besides, the treatments that have promising effects in PCOS are found to reduce these markers such as NF-kB, TNF-α, and interleukin-6 ( Ji et al, 2023 ).…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies suggested that chronic oxidative stress results in inflammatory process, tissue remodeling and apoptosis ( Ye et al, 2023 ). LET n the earlier studies have increased the markers of inflammation and apoptosis, suggesting its mechanism in PCOS ( Areloegbe et al, 2022 ). Besides, the treatments that have promising effects in PCOS are found to reduce these markers such as NF-kB, TNF-α, and interleukin-6 ( Ji et al, 2023 ).…”
Section: Discussionmentioning
confidence: 97%
“…6 Altogether, CVB3 infection might result in the recruitment of neutrophils and macrophages into the pancreatic tissue, aggravating the inflammatory process and leading to cellular apoptosis. 38 LAB has several health benefits, including improving intestinal microbiota, 39 regulating immune function, and antitumor and antiviral effects. L. plantarum , one of the most common LAB, also positively influences the host.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in rats, the use of spironolactone as a metabolic modulator was associated with protection against lipid dysfunction (Areloegbe et al., 2022 ) and in an experimental study, the use of spironolactone with mineralocorticoid antagonistic effects compared to the control group was associated with a significant reduction in body mass loss following starvation only in the first week of use, while this effect was not different from the control group in the following weeks (Pfalzgraff & Skov, 2022 ).…”
Section: Discussionmentioning
confidence: 99%